A marrying man - Stern, G. B. (Gladys Bronwyn), 1890-1973 (Salt Lake City, UT : Project Gutenberg, 2024)
"A Marrying Man" by G. B. Stern is a novel written in the early 20th century. The story revolves around Kathleen Morrison, a woman caught between familial expectations and her own desires as she navigates the complexities of romance and societal norms during a time when marriage was often viewed as a woman's ultimate goal. The narrative begins with Kathleen reflecting on her recent escapade in Alpenruh with Gareth Temple, a charming young botanist, hinting at the emotional turmoil that looms ahead as their relationship unfolds. The opening of the novel sets the tone for Kathleen's internal struggle as she returns to an empty house, imbuing her solitude with memories of her idyllic summer with Gareth. As she grapples with feelings of detachment from her mundane life, her conflicting thoughts about marriage become apparent, especially after Gareth's unexpected visit where he expresses his desire to marry her. The dynamic between Kathleen's longing for freedom and Gareth's romantic aspirations introduces themes of love, identity, and the pressures of societal conventions. The stage is thus set for a deeper exploration of their relationship and the ramifications of their choices as they seek to redefine their paths amidst cultural expectations. (This is an automatically generated summary.)
Release date is 2024-10-18
MWS, Mary Meehan and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/Canadian Libraries)
Keywords: Man-woman relationships -- Fiction; England -- Social life and customs -- 20th century -- Fiction